Е-наука на шляху до семантичного Грід. Частина 1: Об’єднання Web- і Грід- технологій - Zgurovskiy, M. Z.; Petrenko, A. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
The evolution of Grid-systems on the way to the so-called semantic Grid, in which information and services have distinct definitions promoting cooperative work for computers and people, has been investigated. Also, the tendency to convention of Grid- and Web-services on the basis of using the service-oriented architecture (SOA), where Web is used as a Grid information infrastructure, is shown.